Evaluation of antioxidant activity of 25 plant seeds used in Iranian folk medicine - E Souri; H Farsam; M Hasani; Z Azimi Kheirabadi (Institue of Medicinal Plants, ACECR, 2003)
Antioxidants are vital substances which possess the ability to protect the body from damage caused by oxidative stress. A variety of antioxidants exist within the body which many of them are derived from dietry sources like fruits, vegetables and teas. This paper describes a test for determination of antioxidant activity of 25 plant seed extracts used in Iranian folk medicine against linoleic acid peroxidation using 1, 3-diethyl-2-thiobarbituric acid as reagent. Some plant extracts including Great plantain, Lettuce, Nutmeg, Common purslane, Cucumber, Fennel, Cumin, Bishop's weed fruit and Myrobalan showed IC50 values of 0.67, 0.57, 0.29, 0.47, 0.05, 0.32, 0.23, 0.56 and 0.61 g respectively which are comparable or lower than IC50 of vitamin E (IC50= 0.59) as a positive control.